Identifying Risk Factors in Storage Tank Construction Projects: A Systematic Review and Validation Through Aiken’s V Method - Masca Indra Triana; Hanie Teki Tjendanie; Retno Hastijanti (International Journal of Mechanical, Electrical and Civil Engineering, 2025)
This study identifies and validates critical risk factors in storage tank construction projects through a Systematic Literature Review (SLR) and expert judgment using Aiken’s V method. Initially, 103 journal articles were screened, with 43 selected for in-depth analysis, revealing 33 causal factors and six key risk categories. A Focus Group Discussion (FGD) involving industry professionals (project managers, QA personnel, safety officers) enriched the findings by incorporating practical insights missing in academic literature. Eight experts then evaluated these factors using Aiken’s V, validating 13 causal factors and four risk factors as highly significant. Key causal factors included Structure Design, Material Delivery, and Foundation Design, while major risk factors were financial loss, non-compliance, workplace accidents, and poor-quality outcomes. The study establishes a structured risk model for storage tank projects, supporting future quantitative risk analysis and mitigation strategies.